Pengaruh Biaya Produksi dan Harga Jual Terhadap Pendapatan Petani Jagung Desa Sugihwaras - M. Ghofur Riyanto; Lingga Yuliana (Master Manajemen, 2024)
This research aims to determine the costs and income of corn farmers in Sugihwaras Village, District. Sugihwaras, Bojonegoro Regency. With this research, it is hoped that it can help farmers’ current problems, recording production costs should start from the planting process until they become corn seeds ready to sell so that from the income we get, we can determine what the production costs will be and ultimately we can calculate profits accurately. , therefore it is also necessary to study production costs. The method used in this research is a qualitative descriptive method. The descriptive method is a method of researching the status of a group of people, an object, a set of conditions, a system of thought, or a class of events in the present. The research results show that by calculating production costs properly and continuously, we can find out the total production costs (Raw Material Costs, Labor Costs, and Factory Overhead Costs) in each season, the production costs per unit and the profits obtained each season.